“A gente só quer ser estranho como todo mundo”: impacto das estratégias de apoio psicopedagógico sobre a trajetória acadêmica de estudantes no ensino superior - Magnago, Clarissa Faverzani (2024)
This study addresses inclusion in Higher Education and seeks to answer the following problem: how do psychopedagogical support strategies impact the development and continuity of students in Higher Education? The general objective is to understand the impact of these psychopedagogical strategies on the academic trajectory of students. In this work, psychopedagogical support strategies refer to the entire set of actions and resources provided by Federal Institutions of Higher Education (IFES) with the aim of assisting students to overcome obstacles that arise during their academic path. The analysis was based on the subjective perspectives of undergraduate students at the Federal University of Santa Maria (UFSM) regarding the psychopedagogical support strategies provided by this institution, as well as the insights from González Rey's Theory of Subjectivity and Psychopedagogy which provided comprehensibility to the topic. The research approach was guided by González Rey's Qualitative Epistemology (1997) alongside with the Theory of Subjectivity and the Constructive-Interpretative Method, which converged to provide a comprehensive and intricate understanding of the subjects, learning, and the research context. The interpretative work conducted by the researcher had an impact on the corollary of meanings that (re)visited constructs and theoretical categories and produced insights in what concerns to the impact of psychopedagogical support strategies on the academic journey of college students. As a result, it was found that psychopedagogical support strategies represent an important range of actions, involving support, acknowledgment of differences among individuals, the possibility of building subjective meanings for student experiences and subjective reconfiguration regarding aspects of academic life. Consequently, they forebode the strengthening of students' self-esteem, promote autonomous and thoughtful processes, and provide support for coping with adverse events which affect the university course. Moreover, in what concerns to learning, they enable the recovery of the subjective and creative potential, perpetuating learning by means of the students’ protagonism in building and organizing college program. In this regard, education under an inclusive perspective and accessibility are priorities of psychopedagogical strategies, ensuring the continuity of the university journey for many students, justifying the existence of students support services within the university environment. Thus it is possible to state that strategies of psychopedagogical support offered to college students benefit their adaptation, development, continuity, as well as major completion, positively impacting their path. Finally, it is hoped that this construction of knowledge reaches and sensitizes the academic community favoring an active posture of subjects to lift barriers to inclusion, strengthening the fight against prejudice and the stand for autonomy, as well as the construction of senses by and with the students.